Intensity Measure Based on a Smooth Inelastic Peak Period for a More Effective Incremental Dynamic Analysis - Juan Carlos Vielma; Maria Cristina Porcu; Nelson López (Applied Sciences, 2020)
The Incremental Dynamic Analysis (IDA) assesses the global collapse capacity of a structure by plotting its maximum inelastic response, obtained through a non-linear time-history analysis, versus the scaled intensity of different input earthquakes. The seismic intensity is often measured through the spectral acceleration at the fundamental elastic period. However, this can produce highly variable results. An alternative method is presented in this paper that relies on the elongated period, calculated either from the Fourier spectrum of the acceleration at a target building point (inelastic peak period) or from a smooth Fourier spectrum (inelastic smooth peak period). By referring to a reference reinforced concrete building and to a set of 10 spectrum-consistent earthquakes, the paper presents the results of a wide investigation. First, the variation in the elongated period as a function of the seismic intensity is discussed. Then, the effectiveness of the proposed method is assessed by comparing the IDA curves to those obtained through the elastic period or through approximate values of the elongated period given in the literature. The results show that the alternative IDA procedure generates curves with less-dispersed collapse thresholds. A statistical analysis shows significant improvements in the results when the inelastic smooth peak period is adopted.